Assessment of urinary podocalyxin as a marker of glomerular injury in obesity‐related kidney disease in children and adolescents with obesity compared to urinary albumin creatinine ratio. Issue 4 (2nd April 2021) - Musa, Noha; Ramzy, Tarek; Hamdy, Ahmed; Arafa, Noha; Hassan, Mona
Summary: Obesity increases the risk of chronic kidney disease in children. Our aim was to assess urinary podocalyxin (PCX) in children and adolescents with obesity as a potential marker of obesity‐related kidney disease (ORKD). The current case‐control study included 128 children with obesity compared to 60 non‐obese age and sex matched controls. Study population were subjected to full history taking as well as thorough physical examination. Urine samples for albumin creatinine ratio (uACR) and PCX were collected from the study population as well as blood samples for assessment of serum creatinine and fasting lipid profile. A statistically significant difference was found between cases and controls regarding urinary PCX ( P  < .001) and uACR ( P  = .021). A statistically significant positive correlation was found between uACR and weight SD score (SDS), body mass index SDS, waist circumference, estimated glomerular filtration rate, triglycerides (TG) as well as urinary PCX, whilst urinary PCX correlated significantly with obesity duration and uACR. Cases with microalbuminuria had a statistically significant higher waist circumference, waist‐hip ratio, fat percentage, TG and urinary PCX compared to those with normal uACR ( P  = .042, .034, .05, .018 and .036 respectively). Urinary PCX showed 83.3% sensitivity and 74% specificity in detection of albuminuria. Urinary PCX was increased significantly in children with obesity making it a potential sensitive marker of ORKD in children.